A public–private partnership to reduce tuberculosis burden in Akwa Ibom State, Nigeria. Issue 2 (June 2015) - Asuquo, Anne E.; Pokam, Benjamin D. Thumamo; Ibeneme, Emmanuel; Ekpereonne, Esu; Obot, Valerie; Asuquo, P.N.
Abstract Background Tuberculosis (TB) infection and spread are preventable, and TB disease is curable depending on individual and community knowledge of causes of the disease, mode of prevention and cure. An earlier educational intervention carried out in Akwa Ibom State (AKS) of Nigeria in 2006 created awareness of the disease and improved utilization of orthodox medical facilities of residents in 34 communities who had symptoms of TB. Objective The overall aim of this program is to reduce the burden of TB disease in 18 communities of AKS through educational intervention, TB case detection and integration into the State National Tuberculosis and Leprosy Control Programme (NTBLCP), as well as build laboratory capacity to improve TB case detection and control. Methods Prior to the educational intervention in each community, standard pretested questionnaires were administered to residents to test their knowledge, attitudes and practices concerning TB. Information about causes, symptoms and prevention of TB was disseminated in community town halls, churches, markets and schools. Individuals who were coughing for three weeks or more were investigated for TB following clinical examination by a physician. Three sputum samples (spot-morning-spot) were obtained from each individual and examined microscopically for the presence of acid-fast bacilli (AFB) using the Ziehl–Neelson staining technique. Those with positive AFB results were integrated into the existing NTBLCP treatment facilities for immediate commencement of Directly-Observed Therapy Short Course (DOTS). Treatment outcome was monitored by retesting patients' sputum after two, five and seven months. Two new laboratories were facilitated while existing laboratory capacity was built by providing higher resolution microscopes, power generating plants, refrigerators, locally-fabricated incinerators and furnishing of staff offices. The program was facilitated by a public–private partnership. Effective Health Care Alliance Research Programme (EHCARP-Nigeria), in collaboration with Nigeria National Petroleum Cooperation and Mobil Producing Nigeria Unlimited (NNPC/MPN) Joint Venture, utilized health personnel from the Akwa Ibom State NTBLCP who conducted laboratory testing and supervised the treatment. Results The 916 responses to the questionnaires showed that 65.3% (549/841) correctly identified that TB is airborne, and 86% (749/871) were aware that TB could be cured by anti-TB medication. Responses to care-seeking attitudes were provided by 123 respondents. Of this number, fear of stigmatization was the reason for 31% (38) seeking care in unorthodox facilities, while 43.1% (53) did not believe that orthodox medicine could cure their symptoms. Of the 374 detected cases, 9 did not commence treatment. Hence, 365 were placed on DOTS; 36 defaulted, while 11 either died or failed to convert after the seventh month. At the end of month 8, cure was achieved for 87.1% (318). Conclusion Although the previous intervention may have contributed to the good knowledge about TB and care-seeking attitudes displayed by respondents in the communities, sustaining active case finding through public–private partnership can go a long way to reduce TB burden, especially in rural communities where healthcare systems are generally weak or inadequate. Adequate funding of TB control activities is critical in eliminating TB as a public health problem, and the private sector participation such as this is a welcome development.